Perception of service quality among Malaysian university recreational fitness center users - Yusof, Aminuddin; Popa, Arporn; Soh, Kim Geok (Human Resource Management Academic Research Society, 2018)
The purpose of this study was to examine user’s perceptions of service quality and future intention to use campus recreation fitness center in Universiti Putra Malaysia. Data were collected from 200 students and staff of the university (males = 140, females = 60) who frequently used the campus recreation fitness center. The questionnaire consisted of items based on the Likert-scale Service Quality Assessment Scale (SQAS) developed by Lam, Zhang and Jensen (2005). Behavioral intention is based on three questions modified from Cunningham and Kwon (2003). The results showed that recreation fitness center users are satisfied with the overall staff service quality (m=34.14) and fitness facility service quality (m=34.14), but moderately satisfied with overall facility service quality (m=30.77) and overall program service quality (m=24.44). The findings indicated UPM recreation fitness center users have a high intention (m=4.02) to recommend the recreation center to other people and to renew their membership. The result also shows overall staff service quality (ß = .288 p < .05) and overall facility service quality (ß = .251, p <. 05) contribute significantly towards predicting behavioral intention. This means recreation fitness center users in UPM will continue their membership in the future or suggest other people to become members if they perceived the recreation fitness center as being conveniently located as well as user friendly in terms of safety and parking.